Production of lignocelluloses from palm oil empty fruit bunch - Siti Murni, Mohamad Khadri (2010)
Lignocelluloses were a significant new value added product especially for composite industries. The method of alkali and acid treatment was used in order to produces lignocelluloses from palm oil empty fruit bunch. This research obtained to identify the effect of temperature, size of palm oil empty fruit bunch and concentration of acid on production of lignocelluloses yield. The sample of palm oil empty fruit bunch was treated by sodium hydroxide and hydrochloric acid. Sodium hydroxide was used in order to breakdown all the lignin bonding in sample of palm oil empty fruit bunch. Hydrochloric acid was used as a bleaching treatment for lignocelluloses produces. The result shows the smallest size of palm oil empty fruit bunch was resulted high yield of lignocelluloses produces that was 80%. The lowest concentration was decrease the yield of lignocelluloses production that was 40%. Characteristic of lignocelluloses was found using SEM, TGA and FTIR. The morphological structure of lignocelluloses has been analyzing using SEM. The biggest sample of palm oil empty fruit bunch was resulted no breakage and better surface lignocelluloses produces. More stable structure was degrade at higher temperature that was resulted from TGA analyze. There are three functional groups consist in this lignocelluloses that were N(C2H5)4, C-C=C and O-H.